Performance Audit of National Disease Control Programme in Tamil Nadu (1996-2001) - CAG of India (CAG of India, 2002)
Tuberculosis and Blindness are two major diseases which are widely prevalent in the State. National Tuberculosis Control Programme was implemented in the State since 1962 to control Tuberculosis. A revised strategy called Revised National Tuberculosis Control Programme was implemented from 1993 with the objective of achieving cure rate of over 85 per cent through Directly Observed Treatment Short Course Chemotherapy (DOTS). The envisaged cure rate was not achieved in Chennai city and Cuddalore even during 1999-2000. The DOTS was not introduced in 7 districts and implemented late in 23 districts. There were shortfalls in sputum examination, anti-TB drugs were not available at times, follow-up of treatment was poor and treatment was discontinued mid-way in several cases. Inadequate sputum culture facilities and shortage of staff also contributed to poor performance. National Blindness Control Programme from 1976 and a World Bank Assisted Cataract Blindness Control Project from 1994 were being implemented in the State with the goal of reducing prevalence of blindness to 0.3 per cent by 2000 AD. As the physical targets for performing cataract surgeries were fixed by Government of India arbitrarily without taking into account all the parameters, the backlog of cataract surgeries in the State was 0.9 per cent as of March 2001 as against the envisaged rate of 0.3 per cent. The main reasons for the high prevalence rate were poor performance under Government Sector mainly due to less number of cataract operations performed by the surgeons and poor performance of Ophthalmic Assistants in mobilising and enrolling patients for surgeries, poor utilisation of funds under consumables, IEC activities and poor follow-up.
For the Period 1996-97 to 2000-01